Strategic Encounters in Innovation and Regulation: Healthcare Transformation in the Era of Digital Connectivity - Mendonça, Sandro (2022)
Mendonça, S., Damásio, B., Santiago, F., Chen, M., Santos, A. B., Cunha, M. P. E., & Nicita, A. (2022). Strategic Encounters in Innovation and Regulation: Healthcare Transformation in the Era of Digital Connectivity Comment on "What Managers Find Important for Implementation of Innovations in the Healthcare Sector – Practice Through Six Management Perspectives". International Journal of Health Policy and Management, 1-4. https://doi.org/10.34172/ijhpm.2022.7271 -----------Funding: Sandro Mendonça acknowledges support by FCT (Fundação para a Ciência e a Tecnologia), Portugal, by the Business Research Unit (BRU-IUL) and by UECE-REM (Research Unit on Complexity and Economics). BRU-IUL also benefited from grants UID/GES/00315/2013, UIDB/00315/2020; UIDB/05069/2020; PTDC/EGE-ECO/30690/2017 and is part of the project PTDC/EGE-ECO/30690/2017. Sandro Mendonça concluded the paper while he was Visiting Professor at the Dept. of Econoimics of the University of Insumbria, Italy, and he thanks the institution for the research context and support. Bruno Damásio acknowledges the financial support provided by FCT under the project UIDB/04152/2020 - Centro de Investigação em Gestão de Informação (MagIC). Martin Chen acknowledges the research context provided by the doctorate in management developed between ISCTE-IUL, Portugal, and the Southern Medical University, China. Miguel Cunha acknowledges funding by FCT (UID/ECO/00124/2019, UIDB/00124/2020 and Social Sciences DataLab, PINFRA/22209/2016), POR Lisboa and POR Norte (Social Sciences DataLab, PINFRA/22209/2016).